EFFECT OF FATTENING PERIODS ON BODY WEIGHT AND DIMENSIONS AND PREDICATION OF TOTAL WEIGHT GAIN IN LOCAL JANOBI CALVES - Ali A. Al-Talib (Mesopotamia Journal of Agriculture)
This experiment was conducted in the farms of Animal Resource at College of Agriculture and Forestry, Mosul University using some farm records. 18 calves were used in this study, these calves were raised for a period of (140) days which include five consecutive fattening periods to study the effect of these periods on some growth and body dimensions traits (live body weight, heart girth, body length, fore and rear height, fore and rear deepness, fore and rear thickness). Results observed that highly significant effect (P<0.01) of fattening period on live body weight and other body dimensions traits. Live body weight was (234.5 Kg.), other traits were (143.5, 122.5, 108.0, 112.5, 51.31, 46.83, 33.0 and 34.83 cm) respectively. Results also indicated there were positive and significant correlation coefficient (P<0.01) between live body weight and other body measurements, these estimates were (0.9445 , 0.8189 , 0.9047 , 0.9094 , 0.9117 , 0.8660 , 0.9230 , 0.9205) respectively. Stepwise regression analysis showed the possibility of predicting total weight gain by using heart girth and body length.